Extracorporeal Membrane Oxygenation (ECMO) for Hypothermic Cardiac Deterioration: A Case Series. Issue 5 (5th August 2016) - Niehaus, Matthew T.; Pechulis, Rita M.; Wu, James K.; Frei, Steven; Hong, John J.; Sandhu, Rovinder S.; Greenberg, Marna Rayl
Abstract: Accidental hypothermia can lead to untoward cardiac manifestations and arrest. This report presents a case series of severe accidental hypothermia with cardiac complications in three emergency patients who were treated with extracorporeal membrane oxygenation (ECMO) and survived after re-warming. The aim of this discussion was to encourage more clinicians to consider ECMO as a re-warming therapy for severe hypothermia with circulatory collapse and to prompt discussion about decreasing the barriers to its use. MT Niehaus, RM Pechulis, JK Wu, S Frei, JJ Hong, RS Sandhu, MR Greenberg .Extracorporeal membrane oxygenation (ECMO) for hypothermic cardiac deterioration: a case series .Prehosp Disaster Med .2016 ;31 (5 ):570 –571 .